Empowerment of Small and Micro Enterprises (SMEs) in Indonesia: The Impact Venture Capital Assistance, Entrepreneurial Orientation, and Digital Transformation on the Performance of SMEs - Saefudin; Arbianti, Siska (Journal of Management Studies and Development, 2024)
This study investigates the impact of venture capital assistance from LazisMu, entrepreneurial orientation, and digital transformation on the performance of Micro Small Enterprises (SMEs) in Karanganyar Regency. A quantitative approach was used by collecting data from 122 SME respondents who received assistance from LazisMu and have adopted digitalization in the marketing of their products. The data was analyzed using the Smart PLS method to test the relationship between variables. The results showed that business capital assistance from LazisMu has a significant effect on SME performance. However, entrepreneurial orientation has no significant effect. In contrast, digital transformation has a significant impact by improving the operational efficiency and business strategy of SMEs, helping them compete more effectively in a competitive market. This research provides important insights for LazisMu policies and similar institutions to support SMEs more effectively with follow-up research and qualitative approaches to understand more deeply the influence factors.